Instantaneous Response of Wide Area Intrusion Sensor With Long Haul Monitoring Capability - Pua, C.H.; Chong, W.Y.; Ahmad, Harith (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Current optical based wide area intrusion sensors are very limited due to either a complicated setup, expensive facilities, or long data acquisition time. Taking advantage of acoustic wave on the laser dynamics behavior of erbium-doped fiber laser (EDFL), an intrusion sensor with sensing length up to 25 km was demonstrated in this letter. Different from an optical time domain reflectometer (OTDR) based vibration sensor that needs long data acquisition time to obtain average value from multiple scans, this setup provided instantaneous response to the monitoring system as soon as the surrounding area of the sensor is triggered by vibration activities. As the dynamic behavior is directly detected as a large optical intensity fluctuation, hence conventional photo-detector and digital oscilloscope are the only facilities needed in the monitoring system, which make the setup very simple and cost effective.